Penalaran aljabar siswa dalam menyelesaikan soal sistem pertidaksamaan linear dua variabel - Badriyah, Lailatul (Maliki Interdisciplinary Journal, 2025)
Mathematics has an important role in developing the ability to think critically, logically, systematically, and creatively. One of the skills that support mastery of mathematics is algebraic reasoning. This study aims to describe students’ algebraic reasoning in solving two-variable linear inequality system problems based on three aspects according to Van de Walle, namely generalization, symbolic representation, and relationship exploration. This study used a descriptive qualitative approach with data collection techniques in the form of observation, document analysis, and interviews with two subjects. The results showed that both subjects were able to present mathematical models and draw SPtLDV graphs, although there were deficiencies in compiling tabular representations; and stating complete variable boundaries. In the relationship exploration aspect, the subjects determined the solution point from the graph, but only one subject realized the substitution alternative after being given a stimulus. Meanwhile, generalization ability was still limited because the conclusions drawn did not cover all the information in the problem. These findings indicate the need for emphasis on developing generalization ability and symbolic reflection in mathematics learning.